Análise tafonômica de osso de mamíferos marinhos provenientes de encalhes no litoral setentrional do Estado do Rio Grande do Norte no semi-árido Nordestino, Brasil - Dantas, Camilo Chagas (2017)
Taphonomic studies reveals important information about how the environment affects the remains of organisms during the process of decaying. This approach can be used for the study of both ancient and recent organisms. The use of taphonomic techniques to study recent marine mammals were underused, despite its potential. This work aims to study bone material of marine mammals in search of marks left by post-mortem processes related to biotic and abiotic environmental factors in the northern cost of Rio Grande do Norte State, Brasil. According to the taphonomic signatures found in the bone material it was identified weathering processes, abrasion, necrophagy, breaks, taphonomic feedback and human actions. For the northern coast of Rio Grande do Norte skulls have better representation in strandings of marine mammals, but vertebrae have greater reliability for faunal survey. The dynamic tidal influences directly on the samples, acting as a carrier and modifying factor. Also according to the taphomonic signatures found the study area has great heterogeneity regarding the environmental dynamics that produce the signatures studied, adjacent areas can produce different signatures and distant areas can produce similar signatures